Current concepts and novel targets in advanced pancreatic cancer. Issue 2 (30th October 2012) - Michl, Patrick; Gress, Thomas M
Abstract : Pancreatic cancer remains one of the most aggressive tumours with a 5-year survival rate of less than 5%. The dismal prognosis of this tumour entity that is associated with a high degree of drug resistance has not changed over the past decades. Since 1997, gemcitabine-based regimens have been the therapy of choice for advanced pancreatic cancer. Recently, however, new combination chemotherapy regimens achieved a significant survival benefit compared to gemcitabine-based therapies. In addition, novel approaches to improve drug delivery are currently being developed, and new drugs targeting signalling pathways both within the tumour cells and the tumour microenvironment are undergoing preclinical and clinical validation. Furthermore, efforts are being made to identify predictive markers for individualised treatment approaches based on molecular tumour characteristics. This review provides an overview on current and emerging concepts as well as novel targets for systemic treatment of advanced pancreatic cancer. Combination therapies incorporating drugs directed against these new targets may open new avenues for improving the efficacy of current treatment approaches and overcoming the devastating prognosis of pancreatic cancer patients.